2023
DOI: 10.20517/mtod.2023.20
|View full text |Cite
|
Sign up to set email alerts
|

Non-metabolic causes of steatotic liver disease

Patrik Nasr,
Cecilia Jönsson,
Mattias Ekstedt
et al.

Abstract: Hepatic steatosis is caused by exaggerated hepatic lipid accumulation and is a common histological and radiological finding. Non-alcoholic fatty liver disease (NAFLD), or metabolic dysfunction associated steatotic liver disease (MASLD), is highly associated with metabolic syndrome and represents the most common cause of hepatic steatosis. However, since several comorbidities, lifestyle factors, and drugs can cause hepatic steatosis, MASLD is, to some extent, a diagnosis of exclusion. Nevertheless, initiatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…An important caveat is that previous studies identified patients according to the NAFLD definition. There is a significant overlap between NAFLD and MASLD, with both diagnoses requiring the presence of hepatic steatosis [7,8] . In MASLD, the presence of at least one cardiometabolic risk factor is required for the diagnosis [1] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important caveat is that previous studies identified patients according to the NAFLD definition. There is a significant overlap between NAFLD and MASLD, with both diagnoses requiring the presence of hepatic steatosis [7,8] . In MASLD, the presence of at least one cardiometabolic risk factor is required for the diagnosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…In MASLD, the presence of at least one cardiometabolic risk factor is required for the diagnosis [1] . Implementing this definition, a study investigated 1,333 patients at Swedish university hospitals with confirmed NAFLD and found that only 4 patients (0.3%) did not meet the criteria for a diagnosis of MASLD [7] . Similarly, utilizing proton-magnetic resonance spectroscopy, Song et al recently reported a minimal difference in the prevalence of NAFLD (25.6%) and MASLD (26.7%) in 1,106 random persons from Hong Kong [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low testosterone levels in males have been linked with steatotic liver disease, independently of type 2 diabetes mellitus, insulin resistance, and BMI [39] .…”
mentioning
confidence: 99%